Technical Improvement and Application of Hydrodynamic Gene Delivery in Study of Liver Diseases - Huang, Mei; Sun, Rui; Huang, Qiang; Tian, Zhigang (Frontiers in Pharmacology, 2017)
Development of an safe and efficient in vivo gene delivery method is indispensable for molecular biology research and the progress in the following gene therapy. Over the past few years, hydrodynamic gene delivery with naked DNA has drawn increasing interest in both research and potential clinic applications due to its high efficiency and low risk in triggering immune responses and carcinogenesis in comparison to viral vectors. This method, involving intravenous injection (i.v.) of massive DNA in a short duration, gives a transient but high in vivo gene expression especially in the liver of small animals. In addition to DNA, it has also been shown to deliver other substance such as RNA, proteins, synthetic small compounds and even viruses in vivo. Given its ability to robustly mimic in vivo hepatitis B virus (HBV) production in liver, hydrodynamic gene delivery has become a fundamental and important technology on HBV studies in our group and many other groups. Recently, there have been interesting reports about the applications and further improvement of this technology in other liver research. Here, we review the principle, safety, current application and development of hydrodynamic delivery in liver disease studies, and discuss its future prospects, clinical potential and challenges.